The Role of Testosterone in the Treatment of Castration-Resistant Prostate Cancer. Issue 5 (September 2016) - Drazer, Michael W.; Stadler, Walter M.
Abstract : Abstract: Most men with metastatic prostate cancer who are treated with androgen deprivation therapy will eventually develop castration-resistant disease. In this review, we examine the molecular mechanisms that constitute castration resistance and how these processes may be exploited using testosterone-based therapies. We detail how the utilization of superphysiologic doses of testosterone at regular intervals, followed by a rapid clearance of testosterone through continued chemical castration, also known as bipolar androgen therapy, offers an especially promising therapeutic approach. We investigate the historical basis for this modality, detail recent early-phase clinical trials that have demonstrated the feasibility and efficacy of this treatment, and describe an ongoing clinical trial comparing this modality to a currently accepted standard of care, enzalutamide, for castration-resistant prostate cancer. Finally, we explore how this treatment modality will continue to be refined in the future.